2011
DOI: 10.1093/ntr/ntr180
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Nicotine Dependence in U.K. Resident Yemeni Khat Chewers: A Cross-Sectional Study

Abstract: In this study, smoking prevalence was high. Smoking increased during khat chewing. Nicotine dependence levels correlated positively with khat dependence levels, while higher social participation reduced nicotine dependence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
57
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(61 citation statements)
references
References 51 publications
3
57
0
Order By: Relevance
“…[60][61][62] In a study of 204 male Qat chewers identified from Qat outlets in the UK, 21% used tobacco only when chewing Qat, and 44% were daily cigarette smokers. 63 While between 12% and 30% Qat chewers reported initiations of tobacco smoking with Qat chewing, apparently Qat is also a "getaway" from tobacco smoking.…”
Section: Qat Chewing and Tobacco Smokingmentioning
confidence: 99%
See 1 more Smart Citation
“…[60][61][62] In a study of 204 male Qat chewers identified from Qat outlets in the UK, 21% used tobacco only when chewing Qat, and 44% were daily cigarette smokers. 63 While between 12% and 30% Qat chewers reported initiations of tobacco smoking with Qat chewing, apparently Qat is also a "getaway" from tobacco smoking.…”
Section: Qat Chewing and Tobacco Smokingmentioning
confidence: 99%
“…20 The co-occurrence of Qat chewing and tobacco smoking is increasing and is reported mainly amongst Qat chewers in the diasporas. 61,63 Women and men may use different tobacco products during Qat sessions, as there are different forms of tobacco (cigarettes smoking, water pipe smoking, and smokeless tobacco Shamma) available in the countries where Qat is used. For example, Nakajima, et al, reported that the number of cigarettes smoked during a Qat session was higher among men than among women, whereas the frequency of water pipe use during the session was higher among women than men.…”
Section: Qat Chewing and Tobacco Smokingmentioning
confidence: 99%
“…Khat is used commonly in East Africa and the Arabian Peninsula (3), with reports indicating that 80-90% of East African males use khat daily and 10-60% of East African females use khat daily (4,5). Khat is also consumed by immigrants from these regions who reside in western countries, including the United Kingdom (UK) and the United States of America (6).…”
Section: Introductionmentioning
confidence: 99%
“…One study reported that 65% of their sample of UK resident Yemeni subjects were regular cigarette smokers and that khat users smoked to enhance the impact of their khat chewing (6). Increased severity of dependence correlated positively nicotine dependence (6).…”
Section: Introductionmentioning
confidence: 99%
“…Socio-demographic characteristics of the sample were collected using a pre-piloted questionnaire (Kassim & Croucher, 2011). Levels (high and low) of cigarette dependence were measured using FTCD (Heatherton et al, 1991) as well as different levels of cigarette dependence (very low, low and medium) (Fagerstrom & Kozlowski, 1990).…”
Section: Methodsmentioning
confidence: 99%